2009
DOI: 10.1159/000255337
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Detection of Cervical Lymph Node Metastases in Papillary Thyroid Cancer: A Surgical Perspective

Abstract: Despite its relatively benign biological behavior, papillary thyroid cancer is frequently associated with cervical lymph node metastases at the time of diagnosis. These metastases have a limited impact on overall survival, but are recognized as a significant risk factor for locoregional recurrence of the disease. This may significantly alter quality of life, and may require further therapeutic interventions which may be associated with increased morbidity. Therefore, preoperative identification of cervical lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(35 reference statements)
0
15
0
1
Order By: Relevance
“…Our results confirmed that US mapping is a reliable tool for detecting affected LNs. With an PPV of 83.82% for the LC and CC together with advantages, such as simplicity, ease in terms of performance, wide availability, comparatively low price, noninvasiveness and lack of radiation, 12 US mapping is an excellent tool for surgery guidance. The relatively low rate of detection of metastatic LNs in the CC might be explained by anatomic limitations in that area of the neck, such as the clavicle, sternum and tracheal air shadow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results confirmed that US mapping is a reliable tool for detecting affected LNs. With an PPV of 83.82% for the LC and CC together with advantages, such as simplicity, ease in terms of performance, wide availability, comparatively low price, noninvasiveness and lack of radiation, 12 US mapping is an excellent tool for surgery guidance. The relatively low rate of detection of metastatic LNs in the CC might be explained by anatomic limitations in that area of the neck, such as the clavicle, sternum and tracheal air shadow.…”
Section: Discussionmentioning
confidence: 99%
“…3,20 Micrometastases (< 2 mm) in patients undergoing prophylactic LN dissection were found in up to 80% of individuals. 12,25 Nevertheless, such micrometastases are not clincially relevant, as palpable lymphadenopathies do not develop in most patients with PTC. On the contrary, patients presenting with macrometastases (> 2 mm) have 5%-40% persistent/recurrent (P/R) disease after surgery, 26,27 which has a tremendous impact on quality of life, and despite the additional therapeutic interventions, 10% of patients die from the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This classification system is composed of 7 major nodal regions (levels or compartments I-VII) and defines a compartment-oriented neck dissection. Sublevel classification is also used when certain zones within the larger levels have independent biologic significance [6,9]. The classification of cervical lymph nodes is schematically described in figure 1.…”
Section: Classification Of Cervical Lymph Nodesmentioning
confidence: 99%
“…Occasionally, skip metastases can occur, but in general lymphatic dissemination occurs in a stepwise fashion [2,3,4,5]. Accurate knowledge of these metastatic patterns, in addition to a detailed and reliable preoperative ultrasonographic lymphatic mapping of the neck, will allow a more selective and rational therapeutic approach in patients with DTC and lymph node metastases, thereby avoiding routine extensive dissections and their associated increased morbidity [6,7]. The aim of this brief report is to summarize currently available data regarding the patterns of cervical lymph node metastasis in patients with DTC; clinical implications for the practicing surgeon will be briefly discussed, with a particular emphasis on the emerging role of compartment-oriented (so-called ‘selective') CLND, based on the findings of preoperative ultrasonographic lymphatic mapping.…”
Section: Introductionmentioning
confidence: 99%